COMPARATIVE STUDY OF INHERITANCE RIGHTS IN ISLAM AND CIVIL LAW: Analysis of Mashlahah and Maqashid al-Syari`ah - OK Muhammad al fadli; Syafruddin Syam; Muhammad Syukri Albani Nasution (JURNAL ILMIAH MIZANI: Wacana Hukum, Ekonomi, dan Keagamaan, 2021)
The division of inheritance in the Malay community of Batubara Regency is carried out under prevailing traditional customs. It makes Faraidh law the final (alternative) way after discovering problems during the distribution of inheritance. This article analyzes the review of maslahah and maqashid ash-syari'ah on normal inheritance distribution for the people of Batubara Regency. This research is field research with an empirical study approach. This study found that customary inheritance distribution for the people of Batubara Regency was carried out in various ways, according to the conditions of each inheritance problem. When a wife dies (heir), the inheritance will be directly divided under Islamic inheritance law's provisions; the distribution period is no sooner than 40 days and a maximum of 6 (six) months. If the husband dies (heir), then generally, the inheritance is not distributed until the wife or mother of the heir dies, the heirs of the father or mother are often neglected, and ownership of the house goes to the youngest child or children who live together the heir during life, control of the inheritance is controlled by the eldest son. The customary practice of inheritance distribution for the people of Batubara Regency, which makes the foundation of benefit in the distribution of inheritance in the people of Batubara Regency, is mashlahah mulghah, contrary to the texts of the Koran and the hadiths of the Prophet SAW. In addition, in the maqashid asy-shari'ah scale, it is not achieved regarding the hajiyyat case, namely hifzhul mal Pembagian harta warisan di masyarakat Melayu Kabupaten Batubara dilakukan sesuai dengan kebiasaan adat yang berlaku, dan menjadikan hukum faraidh sebagai jalan akhir (alternatif) setelah ditemukannya masalah sewaktu pembagian harta warisan. Artikel ini menganalisis tinjauan mashlahah dan maqashid asy-syari`ah terhadap praktik pembagian warisan secara adat bagi masyarakat Kabupaten Batubara. Penelitian ini adalah penelitian lapangan (field research), dengan pendekatan kajian empiris (empirical study). Penelitian ini menemukan bahwa praktik pembagian warisan secara adat bagi masyarakat Kabupaten Batubara dilakukan dengan cara beragam, sesuai dengan kondisi masing-masing masalah warisan. Ketika seorang istri meninggal dunia (pewaris), maka harta warisan akan langsung dibagi-bagi sesuai dengan ketentuan hukum waris Islam, jangka waktu pembagian harta warisan paling cepat setelah 40 hari, dan paling lama 6 (enam) bulan. Apabila suami meninggal dunia (pewaris), maka umumnya harta warisan tidak dibagi-bagikan, hingga istri atau ibu dari ahli waris meninggal dunia, ahli waris ayah atau ibu, kerap kali diabaikan, kepemilikan rumah  kepada anak yang paling kecil, atau anak yang tinggal bersama pewaris semasa hidup, penguasaan harta warisan dikuasai oleh anak laki-laki tertua. Praktik pembagian warisan secara adat bagi masyarakat Kabupaten Batubara yang menjadikan kemashlahatan landasan dalam pembagian harta waris di masyarakat Kabupaten Batubara adalah mashlahah mulghah, bertentangan dengan nash Alquran dan hadis-hadis Rasul SAW. Selain itu, dalam timbangan maqashid asy-syari`ah, perihal perkara hajiyyat, yakni hifzhul mal, maka tidak tercapai